The night of the storm : a novel - Parekh, Nishita (Dutton, 2024)
"From debut author Nishita Parekh, a fresh take on the classic locked-room thriller, about a multigenerational Indian American family marooned in a house with a murderer during a hurricane. Hurricane Harvey is about to hit Houston. Meanwhile, single mom Jia Shah is already having a rough week: her twelve-year-old son, Ishaan, has just been suspended from school for getting in a fight. Still reeling from the fallout of her divorce--their move to Houston, her family's disapproval, the struggle to make ends meet on her own--now Jia is worried about Ishaan's future, too. Will her solo parenting be enough? Doesn't a boy need a father? And now their apartment complex is under a mandatory evacuation order. Jia's sister, Seema, has invited them to hunker down in her fancy house in Sugar Land, and despite Jia's misgivings--as Seema's husband, Vipul, has been just a little too friendly with her lately--Jia concedes it's probably the best place to keep Ishaan safe during the hurricane. With Jia's philandering ex scrutinizing her every move, all too eager to snatch back custody of Ishaan, she can't afford to make a mistake. When Vipul's brother and his wife show up on Seema's doorstep, too, it's a recipe for disaster. Grandma, the family matriarch, has never been shy about playing favorites among her sons and their wives. As the storm escalates, tensions rise quickly, and soon someone's dead. Was it a horrible accident or is there a murderer in their midst? With no help available until the floodwaters recede in the morning, Jia must protect her son and identify the culprit before she goes down for a crime she didn't commit--or becomes the next victim..."--